ChemInform Abstract: An Organocatalytic Asymmetric Sequential Allylic Alkylation—Cyclization of Morita—Baylis—Hillman Carbonates and 3‐Hydroxyoxindoles. Issue 6 (11th February 2014) - Wang, Qi‐Lin; Peng, Lin; Wang, Fei‐Ying; Zhang, Ming‐Liang; Jia, Li‐Na; Tian, Fang; Xu, Xiao‐Ying; Wang, Li‐Xin
Abstract The first organocatalytic asymmetric cyclization of the title compounds is presented.